Mitigating cellular aging and enhancing cognitive functionality: visual arts-mediated Cognitive Activation Therapy in neurocognitive disorders - Campisi, Manuela; Cannella, Luana; Celik, Dilek; Gabelli, Carlo; Gollin, Donata; Simoni, Marco; Ruaro, Cristina; Fantinato, Elena; Pavanello, Sofia (Frontiers in Aging Neuroscience, 2024)
The growing phenomenon of population aging is redefining demographic dynamics, intensifying age-related conditions, especially dementia, projected to triple by 2050 with an enormous global economic burden. This study investigates visual arts-mediated Cognitive Activation Therapy (CAT) as a non-pharmacological CAT intervention targets both biological aging [leukocyte telomere length (LTL), DNA methylation age (DNAmAge)] and cognitive functionality. Aligning with a broader trend of integrating non-pharmacological approaches into dementia care. The longitudinal study involved 20 patients with mild to moderate neurocognitive disorders. Cognitive and functional assessments, and biological aging markers -i.e., LTL and DNAmAge- were analyzed before and after CAT intervention. Change in LTL was positively correlated with days of treatment (p =0.0518). LTL significantly elongated after intervention (p =0.0269), especially in men (p =0.0142), correlating with younger age (p =0.0357), and higher education (p =0.0008). DNAmAge remained instead stable post-treatment. Cognitive and functional improvements were observed for Copy of complex geometric figure, Progressive Silhouettes, Position Discrimination, Communication Activities of Daily Living—Second edition, Direct Functional Status (p < 0.0001) and Object decision (p =0.0594), but no correlations were found between LTL and cognitive gains. Visual arts-mediated CAT effectively mitigates cellular aging, especially in men, by elongating LTL. These findings underscore the potential of non-pharmacological interventions in enhancing cognitive and functional status and general well-being in dementia care. Further research with larger and longer-term studies is essential for validation.